On Subjectivity and Survivance: Re-reading Trauma through The Heirs of Columbus and The Crown of Columbus - Madsen, Deborah Lea (University of Nebraska Press (Lincoln), 2008)
In this essay, I take as my starting point dominant Western theories of trauma that deploy paradigms of trauma therapy that are based on the "recovery" of a singular and homogenous subjectivity. The cultural bias of this assumption, that reassimilation or reintegration of a fragmented ego must necessarily be the object of therapy, becomes clear in the context of Gerald Vizenor's concept of survivance, which places productively in question the stability and desirability of this notion of selfhood in a Native American Indian context. The Western understanding of trauma emerges as a narrative of dominance, but it is revealed as such only when we substitute the term "survival" of trauma with that of "survivance" in the face of historical trauma. In what follows, I want to ask how does a "postindian" subject, such as Gerald Vizenor describes, survive? Is "recovery" from historical trauma either desirable or possible? And how is Native subjectivity situated in relation to the dominant American multiculture, within the context of post-contact historical trauma? My texts for this investigation are two prominent but very different Anishinaabe, Chippewa or Ojibwe novels written in anticipation of the Columbian quincentenary: Gerald Vizenor's The Heirs of Columbus (1991) and The Crown of Columbus (1991) by Louise Erdrich and Michael Dorris. The latter offers us a survivor narrative; in contrast, Vizenor's novel offers a narrative of survivance.